Mechanism of HIF-1α Promoting Malignant Development of Nasopharyngeal Carcinoma by Upregulating PD-L1 Under Hypoxic Conditions - JIANG Doudou (Zhongliu Fangzhi Yanjiu, 2021)
Objective To explore the mechanism of HIF-1α promoting malignant development of nasopharyngeal carcinoma by upregulating PD-L1 expression under hypoxic conditions. Methods CNE2 cells were divided into normoxia (20%O2), hypoxia (1%O2), HIF-1α-siRNA+hypoxia and NC-siRNA+hypoxia groups. Cell proliferation, apoptosis, the mRNA levels of HIF-1α, STAT3 and PD-L1, the protein levels of HIF-1α, PD-L1, STAT3 and STAT3 phosphorylation were detected by MTT assay, flow cytometry, RT-PCR and Western blot, respectively. Results Cell proliferation of hypoxia group was significantly higher than that of normoxia group (P=0.000). The cell proliferation rate of HIF-1α-siRNA+hypoxia group was significantly lower than those in other groups (P=0.000). The apoptosis rate of HIF-1α-siRNA+hypoxia group was remarkably higher than those in other groups (P=0.001). RT-PCR detection showed that the mRNA levels of HIF-1α, PD-L1 and STAT3 in the HIF-1α-siRNA+hypoxia group were significantly lower than those in hypoxia group and NC-siRNA+hypoxia group. The protein expression of HIF-1α, PD-L1 and STAT3 showed similar tendency in Western blot assays compared with the mRNA levels. The pSTAT3 protein expression level in HIF-1α-siRNA+hypoxia group was significantly lower than those in hypoxia group and HIF-1α-siRNA+hypoxia group (P=0.001). Conclusion Under hypoxic microenvironment, HIF-1α may up-regulate the expression of PD-L1 through STAT3, thereby promoting the immune escape of cancer cells, leading to the malignant development of nasopharyngeal carcinoma.